The Effect of Number of Members, Own Capital, External Capital and Business Volume on the Residual Results of Cooperative Business in West Java Province 2018-2020 - Yaqzah, Moch. Wahyu; Sumarsono, Hadi (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
Cooperatives as an institution with member welfare are the main goal through the process of dividing the remaining operating results (SHU). This study will examine the resulting influence on aspects of cooperatives such as the number of members, owner's capital , external capital, and business volume on SHU. Cooperatives throughout West Java Province were selected as research subjects, with data acquisition using Time Series with Cross Sections in 26 cities/districts of West Java Province in 2018-2020. The quantitative method uses a descriptive approach and panel data regression analysis, which succeeded in finding that number of members is partially positively related to the remaining operating results but has no significant effect. Owner’s capital and business volume can positively and significantly affect the remaining operating results. Meanwhile, external capital creates a significant negative impact on SHU. In a simultaneous study, all independent variables significantly positively influenced the SHU.